2016
DOI: 10.1016/j.amepre.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sugar-Sweetened Beverage Warnings

Abstract: Introduction California, New York, and the cities of San Francisco and Baltimore have introduced bills requiring health-related warning labels for sugar-sweetened beverages. This study measures the extent to which these warning labels influence adolescents’ beliefs and hypothetical choices. Design Participants completed an online survey in which they chose a beverage in a hypothetical vending machine task, rated perceptions of different beverages, and indicated interest in coupons for beverages. Data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
85
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 9 publications
6
85
1
Order By: Relevance
“…The findings from this study are consistent with evidence regarding the efficacy of aversive images for discouraging unhealthy dietary choices ( Hollands and Marteau, 2016 ; Hollands et al, 2011 ), as well as prior findings of the few studies on the use of warning labels on SSBs ( Lee et al, 2017 ; Bollard et al, 2016 ; Gray et al, 2011 ; Vanepps and Roberto, 2016 ; Roberto et al, 2016 ). The effect size of warning labels overall on SSB selection is similar to that obtained in the previous research based on which this study was powered ( Roberto et al, 2016 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The findings from this study are consistent with evidence regarding the efficacy of aversive images for discouraging unhealthy dietary choices ( Hollands and Marteau, 2016 ; Hollands et al, 2011 ), as well as prior findings of the few studies on the use of warning labels on SSBs ( Lee et al, 2017 ; Bollard et al, 2016 ; Gray et al, 2011 ; Vanepps and Roberto, 2016 ; Roberto et al, 2016 ). The effect size of warning labels overall on SSB selection is similar to that obtained in the previous research based on which this study was powered ( Roberto et al, 2016 ).…”
Section: Discussionsupporting
confidence: 88%
“…It is worth noting, however, that although the disease image label was rated as less acceptable than other labels, it was considered more acceptable than not having any label. This mirrors recent findings showing support for a policy to place warning labels on SSBs ( Vanepps and Roberto, 2016 ; Roberto et al, 2016 ) and is consistent with evidence that labelling intervention for SSBs are typically better supported by the public, at least compared to more intrusive policies such as taxation ( Gollust et al, 2014 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Though the effect of an HSR label on consumers’ food and beverage choices was found to be weak in an experimental online scenario [ 21 ] and real-world setting studies [ 22 , 23 ]. The finding that the graphic warning labels might be more effective in changing beverage selection compared to other labels is in line with other online choice scenario studies [ 24 – 26 ]. However, implementation of such warning labels in the real-world setting might be challenging due to strong opposition from the SSB and sugar industries [ 27 , 28 ].…”
Section: Introductionsupporting
confidence: 89%
“…More recently, researchers have been investigating whether the use of warning labels could also be effective in reducing sugar-sweetened beverage consumption. Online studies have found that people report lower intentions to choose a sugar-sweetened beverage when a text warning label is presented compared with no warning label (11,12). However, in line with the literature on cigarette smoking, graphic warning labels may be more effective in promoting behaviour change.…”
Section: Introductionmentioning
confidence: 88%